Problematyka finansów samorządu terytorialnego w Polsce - Komar, Andrzej (Wydział Prawa i Administracji UAM, 1990)
The reinstatement of territorial self-government in Poland makes it necessary to solve some basic problems in the area of finances. Three of such problems have been dealt with in this article. Firstly, the author outlines the conception of a system of financing the self-government. Secondly, he presents the solutions in the area of financing adopted in the Act on Territorial Government. Thirdly, he evaluates those solutions. Unfortunately, the solutions contained in the said Act are not satisfactory, for they are deprived of a necessary context. In particular, the sources, of budget revenues of self-government are limited what may negatively affect the self- -government's capacity to carry out its tasks. Besides, the Act bears the marks of legislative haste. Therefore, the article points to the urgent need of amending the statutory provisions in the section regulating the finances of self-government. However, the legislative process should be preceded by the formulation of the conception of local finances, compatible with the European standards. The article presents such a conception and suggests ways of its inclusion into legislation.
The problems of finances of territorial self-government